Las lenguas de la filosofía: una guía para la diáspora - Valle, Gabriel (2017)
The author focuses on one of the most pressing problems Philosophy has always been dealing with: the differences in the philosophical vocabulary of the languages of Europe. The paper is chiefly a remark about a lexicon: Vocabulaire européen des philosophies: dictionnaire des intraduisibles (edited by Barbara Cassin in 2004). It has already been translated into several languages. Then Tim Crane’s review of the book is summarized.